KORELASI ANTARA TASK VALUE (NILAI TUGAS) SISWA DENGAN NILAI ULANGAN HARIAN - Satriya, Epik (Unversitas Katolik Santo Thomas, 2021)
This research was conducted at Madrasah Ibtidaiyah Negeri (MIN) 1 Sintang for the 2019/2020 school year. Based on the learning outcome data, it shows student learning scores that are good in the conditions and situations of the Covid-19 pandemic. This research aimed to determine the relationship between the task value of students and the daily test scores of students in class VB MIN 1 Sintang for the 2019/2020 school year. The approach used in this research is quantitative while the research method uses the correlation method. Techniques and data collection tools used in this study were documentation techniques, while the tools were documents. Based on the research results, it was found that the average value of the task value of students from the sample was 81.2. Meanwhile, the students' daily test results obtained an average value of 85.9 in the good category. After the data is calculated statistically, it is obtained that rcount is 0.477, which means that it is in the value range 0.40-0.599 in the medium category. The results of the determinant formula obtained KP = 22.75%. From the significant test results obtained tcount of 3.096 where the error level is 5% or Î± = 0.05 and the degrees of freedom dk = n-2, dk = 32-2 dk = 30, for the ttable value of 2.042. Because tcount > ttable, namely 3.096 > 2.042, then Ho is rejected and Ha is accepted. So that the conclusion is that there is a significant relationship between the task value of students and the daily test scores of students in class VB MIN 1 Sintang for the 2019/2020 school year.